2016
DOI: 10.1007/s40123-016-0058-2
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Improving Patient Comfort During Intravitreal Injections: Results from a Survey-Based Study

Abstract: IntroductionMany ocular diseases require intravitreal injections of pharmacological agents. Optimizing patients’ experiences during injections is important to ensure compliance and maintenance of quality of life. The objective of this study was to identify strategies to help alleviate discomfort during intravitreal injections.MethodsA cross-sectional study surveying 128 patients during clinic visits between 2014 and 2015 in two outpatient Retina Clinics (one academic and one private). Patients receiving an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…These are intended to eliminate any residual or prevent the reoccurrence of subretinal fluid. Regardless of the approach, patients affected with wet AMD find themselves having to endure an indefinite number of repeated intravitreal injections of anti-VEGF drugs, along with their associated risk factors, including the development of endopthalmitis and reduced patient compliance 50, 51, 52, 53, 54…”
Section: Discussionmentioning
confidence: 99%
“…These are intended to eliminate any residual or prevent the reoccurrence of subretinal fluid. Regardless of the approach, patients affected with wet AMD find themselves having to endure an indefinite number of repeated intravitreal injections of anti-VEGF drugs, along with their associated risk factors, including the development of endopthalmitis and reduced patient compliance 50, 51, 52, 53, 54…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving an IVI for the first time should be allocated more time to learn about the injection and monitored for unexpected reactions. Gomez et al studied patient comfort during IVIs and found that favorable strategies were the presence of an extra staff member during the injection, the use of a neck pillow, and the provision of a verbal warning prior to the IVI [34]. When bilateral IVIs were necessary, the majority of the patients preferred to have them performed on the same day [34].…”
Section: Optimizing Patient Comfortmentioning
confidence: 99%
“…Gomez et al studied patient comfort during IVIs and found that favorable strategies were the presence of an extra staff member during the injection, the use of a neck pillow, and the provision of a verbal warning prior to the IVI [34]. When bilateral IVIs were necessary, the majority of the patients preferred to have them performed on the same day [34]. In addition, patients between 30 and 60 years of age preferred to have their hand held during the IVI and to have background music playing during the injection [34].…”
Section: Optimizing Patient Comfortmentioning
confidence: 99%
See 2 more Smart Citations